Detection of drug effects on gastric emptying and contractility using a wireless motility capsule - Rozov-Ung, Inna; Mreyoud, Amjad; Moore, John; Wilding, Gregory E; Khawam, Elias; Lackner, Jeffrey M; Semler, John R; Sitrin, Michael D (BMC gastroenterology, 2014)
Background A wireless motility capsule is a new method for ambulatory assessment of transit times and motility throughout the gastrointestinal tract. The objective of this study was to evaluate the ability of a wireless motility capsule to detect drug effects on gastric emptying time (GET) and gastric contractility. Methods 15 healthy adults were administered in random order saline, erythromycin IV 150 mg, or morphine IV 0.05 mg/kg BW. Subjects ate a standard meal after each infusion, and subsequently ingested the motility capsule. Data were recorded for 8 hours, and the results were analyzed using the manufacturer’s software. Results GET was significantly faster after erythromycin than either saline or morphine. Morphine tended to delay emptying of the capsule compared to saline. There was a trend toward a greater frequency of gastric contractions with erythromycin and a reduced frequency of gastric contractions with morphine that did not reach statistical significance. Conclusions A wireless motility capsule successfully detected acceleration of gastric emptying induced by erythromycin, and retardation of gastric motility caused by morphine. These results indicate that a wireless motility capsule is a promising technique to assess pharmacologic effects on gastric transit and contractility and aid in development of drugs for gastric motor disorders.